The behaviour of nanofluids flooded in printed mini channels when excited by a small electrical potential - Bani Hashim, Ahmad Yusairi; Afandi, Azri Nazran; Mohamad, Imran Syakir; Zainal Abidin, Syazwani; Abdullah, Amira Lateef (Inderscience Publishers, 2020)
This work sought to observe the response of a nanofluid put along in an electrical circuit while seeing the behaviour of the fluid. Would the nanofluids have a characteristic of an electrolyte? Two mini channels were constructed using additive manufacturing approach. The nanofluids were flooded in the channels where they were connected in series with a generic resistor in a low voltage circuit. The fluids' behaviours were observed through the recorded voltage drops at the resistor and also at the channel's start and end points, respectively. The results showed minute currents were flowing in the circuit as the fluids recorded high resistances. Therefore, the nanofluids are naturally high resistance electrolytes. However, the real nature of the fluids exposed to electrical potentials for a longer duration is unknown.